Cost-minimization modeling of venous thromboembolism diagnostics: performing limited compression ultrasound in primary health care reduces costs compared to referring patients to a hospital - Hannula Ossi; Mustonen Anssi; Rautiainen Suvi; Vanninen Ritva; Hyppölä Harri (SPRINGER, 2025)
Background: The aim of this retrospective study was to determine whether diagnosing a deep venous thrombosis (DVT) in primary health care using limited compression ultrasound (LCUS) can save resources compared to referring these patients to hospital. According to the current literature, LCUS is as safe as a standard protocol based on a whole-leg ultrasound (US).
Methods: We created a standardized patient for this cost-analysis model based on 76 patients that were referred to hospital for a suspected DVT. Travel distance to the health care centre and hospital was calculated based on the home address. Hospital costs were acquired from the hospital price list and Finnish legislation. Time spent in the hospital was retrieved from hospital statistics. Time spent in the health care centre and travelling were estimated and monetized based on average salary. The cost of participating physicians attending a US training course was estimated based on the national average salary of a general practitioner as well as the course participation fee. A cost-minimization modeling was performed for this standardized patient comparing the total costs, including private and public costs, of standard and LCUS strategies.
Results: The total costs per patient of standard and LCUS pathways were 1151.52€ and 301.94€ [difference 849.59€ (95% CI 800.21€-898.97€, p < 0.001)], respectively. The real-life costs of these strategies, considering that some patients are probably referred to hospital every year and including training costs, are 1151.53€ and 508.69€ [difference 642.84€ (95% CI 541.85€-743.82€)], respectively.
Conclusion: Using LCUS in diagnosing DVT in primary health care instead of referring these patients to the hospital is shown to save a significant amount of public and private resources.